Genetic diversity in peach cultivars - Matias, Rosana Gonçalves Pires; Bruckner, Cláudio Horst; Oliveira, João Alison Alves; Carneiro, Pedro Crescêncio Souza; Silva, Danielle Fabíola Pereira; Santos, Carlos Eduardo Magalhães (Comunicata Scientiae, 2016)
This study aimed to evaluate the genetic diversity among 28 peach cultivars and two nectarine cultivars, describing the most important characters in the diversity evaluation. The study was developed at the Federal University of Viçosa - Brazil, and the following characteristics were evaluated: fruit mass, suture, equatorial and polar diameters, firmness, soluble solids (SS), titratable acidity (TA), SS/TA, ascorbic acid and carotenoids contents, skin and flesh color (coordinate b* and hue angle - °h). Genetic diversity in peach and nectarine cultivars enabled the formation of seven, six and six groups in the 2011, 2012 and 2013 crop years, respectively. The features that most contributed to this diversity were fruit mass, skin and flesh °h and firmness. The greatest genetic divergence was observed between ‘Marli’ and ‘Rubrosol’, ‘Josefina’ and ‘Maciel’ and ‘Maciel’ and ‘Rubrosol’ during the 2011, 2012 and 2013 crop years, respectively.